THE INCREASE OF EFFICIENCY OF ASSOCIATION OF THE DATA FOR STABILITY AERONAVIGATION SYSRWM IN THE EVENT CORRELATED OBSERVATION GAUSSIAN DENSITY - Слюняєв, О. (Science-based technologies, 2011)
The technique of increase of efficiency of association of the data in case of Gaussian density for the purpose of optimization  of statistically  distributed  revealing  is  considered  and  work  of the  concentrated  processor  which provides faster decision-making uniting decisions of separate receivers.